The Effect of a Community-Based, Primary Health Care Exercise Program on Inflammatory Biomarkers and Hormone Levels - Papini, Camila Bosquiero [UNESP]; Nakamura, Priscila M. [UNESP]; Zorzetto, Lucas P. [UNESP]; Thompson, Janice L.; Phillips, Anna C.; Kokubun, Eduardo [UNESP] (Hindawi Publishing Corporation, 2014)
The aim of this study was to analyze the impact of a community-based exercise program in primary care on inflammatory biomarkers and hormone levels. The 1-year quasiexperimental study involved 13 women (mean age = 56.8 +/- 11.4 years) and it was developed in two basic health care units in Rio Claro City, Brazil. The physical exercise intervention was comprised of two, 60-minute sessions/week. The inflammatory biomarkers were measured at baseline, 6 months, and 1 year. Repeated measures ANOVA analyses indicated that the intervention was effective in reducing CRP and TNF alpha after 1 year compared to baseline and 6 months (P < 0.05). There were no changes in IL10, IL6, and insulin after 1 year. However, leptin significantly increased at 1 year (P = 0.016). The major finding of this study is that a community-based exercise program can result in a decrease or maintenance of inflammatory biomarkers after 1 year, and thus has the potential to be a viable public health approach for chronic disease prevention.